Synthesis and reactivity of osmium and ruthenium PBP–LXL boryl pincer complexes. (14th December 2016) - McQueen, Caitlin M.A.; Hill, Anthony F.; Sharma, Manab; Singh, Suprita K.; Ward, Jas S.; Willis, Anthony C.; Young, Rowan D.
Graphical abstract: The first examples of osmium boryl pincer complexes and their ligand substitution chemistry are described alongside those of the ruthenium analogue. Abstract: The reaction of HB(NCH2 PPh2 )2 C6 H4 -1, 2 with [OsCl(Ph)(CO)(PPh3 )2 ] affords the boryl pincer complex [OsCl(CO)(PPh3 )B(NCH2 PPh2 )2 C6 H4 ]. This complex, and its ruthenium analogue were observed to undergo various reactions involving substitution of the chloride and triphenylphosphine co-ligands to give new complexes [MCl(CO)(CNC6 H2 Me3 )B(NCH2 PPh2 )2 C6 H4 ] (M = Ru, Os), [MH(CO)(PPh3 )B(NCH2 PPh2 )2 C6 H4 ] (M = Ru, Os) and [Ru(κ 2 - S, S ′ - S2 CNEt2 )(CO)B(NCH2 PPh2 )2 C6 H4 ]. The ruthenium complex [RuH(CO)(PPh3 )B(NCH2 PPh2 )2 C6 H4 ] was found to react with carbon disulfide and carbon monoxide to give the complexes [Ru(κ 2 - S, S ′-S2 CH)(CO)B(NCH2 PPh2 )2 C6 H4 ] and [RuH(CO)2 B(NCH2 PPh2 )2 C6 H4 ], respectively, the latter as an apparently interconverting mixture of cis and trans dicarbonyl isomers.